2011
DOI: 10.1117/1.3530077
|View full text |Cite
|
Sign up to set email alerts
|

Vibroacoustic launch analysis and alleviation of lightweight, active mirrors

Abstract: Lightweight, active, silicon carbide mirrors can increase the capability of space-based optical systems. However, launch survival is a serious concern for such systems, with the vibrations and acoustics from launch threatening to damage the optics. Therefore, a dynamic, statespace launch model has been developed with which one can quickly analyze the survival probability of many designs and also directly analyze launch load alleviation techniques. This paper discusses the launch model from which launch stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The disturbing vibration is defined in terms of acceleration power spectral density and applied on the active feet of the DM, in the vertical direction. A typical spectrum [10], normalized to 20 g, is used as shown in Fig. 10.…”
Section: Response To Support Vibrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disturbing vibration is defined in terms of acceleration power spectral density and applied on the active feet of the DM, in the vertical direction. A typical spectrum [10], normalized to 20 g, is used as shown in Fig. 10.…”
Section: Response To Support Vibrationsmentioning
confidence: 99%
“…flexible configurations which would fail a vibration qualification test). A similar study was conducted numerically on a silicon carbide primary mirror (M1) for space telescopes [10]; the authors compared various passive and active vibration alleviation techniques against vibro-acoustic loads and concluded that increasing the damping of the M1 during launch would allow to use better designs of deformable mirrors. Here, we extend these results by implementing numerically and experimentally the piezoelectric resistive and inductive RL shunt on a deformable mirror.…”
Section: Introductionmentioning
confidence: 99%
“…The model used here is a state-space model derived from finite element normal modes analysis. 4,14 The inputs to the model are random vibration and acoustic spectra from the launch vehicle and the outputs of the model are stresses in the elements, resulting in a stress distribution across the mirror. The total input disturbance is 6.2 g for the random vibrations and 145.2 dB for the acoustics.…”
Section: Dynamic Launch Modelmentioning
confidence: 99%
“…More details about the model and launch disturbances can be found in Cohan. 4,14 The stress outputs from this model are validated to the extent possible. They are compared to available data from multiple similar systems and match within 10% in all cases.…”
Section: Dynamic Launch Modelmentioning
confidence: 99%
See 1 more Smart Citation